2012
DOI: 10.1155/2012/347389
|View full text |Cite
|
Sign up to set email alerts
|

The Critical Height of a Liquid Being Drained from the Tank with Bell-Mouth Drain Port

Abstract: Vortexing occurs during draining of liquid from tanks. We studied the critical height of a liquid being drained from tank, that is, the liquid height at the moment when the air-core vortex reaches to the drain port. We firstly performed some experiments for determining the critical height, and then based upon the information obtained from the experiments; a simple analytical expression was derived to predict the critical height. The experimental results show that the vortex suppressor, which is suggested in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(15 citation statements)
references
References 9 publications
3
12
0
Order By: Relevance
“…Moreover, the critical height of 35 mm for 8 l/s, obtained by Mohammadi et al, 25 is not realistic, since 35 mm is lower than siphon height of 38 mm and liquid surface is exposed below 38 mm, which is not a valid result. This large deviation of analytical results 25 from their own experimental data is studied. The height “ h ” of the siphon position above the tank bottom is not included in the analytical model, 25 whereas the model presented in this paper for “critical height of siphon drain in spherical bottom tank” considers this height as “ h ”.…”
Section: Comparison Of Present Results With Reported Experimental And...mentioning
confidence: 89%
See 3 more Smart Citations
“…Moreover, the critical height of 35 mm for 8 l/s, obtained by Mohammadi et al, 25 is not realistic, since 35 mm is lower than siphon height of 38 mm and liquid surface is exposed below 38 mm, which is not a valid result. This large deviation of analytical results 25 from their own experimental data is studied. The height “ h ” of the siphon position above the tank bottom is not included in the analytical model, 25 whereas the model presented in this paper for “critical height of siphon drain in spherical bottom tank” considers this height as “ h ”.…”
Section: Comparison Of Present Results With Reported Experimental And...mentioning
confidence: 89%
“…Mohammadi et al 25 reported experimental data and an analytical model for siphon drain in spherical bottom tanks. For the purpose of comparison, the analytical method developed for “siphon drain from spherical bottom tank” is applied for the same geometry reported by Mohammadi et al 25 The geometrical parameters are h = 0.038 m (26 mm + 12 mm); a = 0.155 m; R =1 m; Q = 8, 10, 14, 18, 21 lit/s (approx.).…”
Section: Comparison Of Present Results With Reported Experimental And...mentioning
confidence: 99%
See 2 more Smart Citations
“…At large value of the angular velocity ratio, bubble ceases to exist. Mohammadi et al (2012) have studied vortex formation employing bell-mouthed drain-port situated at center of the bottom of the test tank along the cylinder longitudinal axis. Authors proposed introduction of multiple suppressor plates under the bell-mouth drain port to prevent vortex formation.…”
Section: Introductionmentioning
confidence: 99%